Analysis of diesel spray dynamics using a compressible Eulerian/VOF/LES model and microscopic shadowgraphy. (15th January 2017) - Ghiji, M.; Goldsworthy, L.; Brandner, P.A.; Garaniya, V.; Hield, P.
Highlights: In-and near-nozzle diesel spray dynamics are investigated. Structure of the jet at early and quasi-steady stages of the injection is analyzed. Starting vortex at early stage of the injection is captured. An LES approach is used for numerical analysis of subsonic and supersonic states. Onset and development of shock waves for high pressure diesel jet are discussed. Abstract: This paper presents numerical and experimental analysis of diesel engine spray dynamics in the region very close to the nozzle exit. Diesel fuel is injected through a single solid cone injector with sharp-edged nozzle inlet. Numerical investigations are conducted in an Eulerian framework by applying a Volume of Fluid interface capturing technique integrated with Large-Eddy Simulation turbulence modelling. Cavitation is modelled, by allowing liquid fuel to flash to gas at the fuel vapor pressure. The computational domain and settings mimic the experimental injector internal geometry and experimental operating conditions. In-nozzle disturbances are qualitatively well modelled by implementing the no-slip condition at the injector walls as well as cavitation and compressibility effects for each phase. A mesh dependency study is conducted with four different grid resolutions. Data are presented around the start of penetration (SOP) and up to the time when shock waves at the gas-liquid interface are well developed, the quasi-steady stage of injection. At SOP, an umbrella-shaped leading edge is captured in both the numerical and experimental studies however only the experimental images demonstrated a semi-transparent cloud of air-fuel mixture at the leading edge. A previously undescribed toroidal starting vortex near the nozzle exit is captured experimentally and numerically. Development of cavitation, down to the end of nozzle hole leads to the detachment of liquid from the nozzle hole walls and subsequently the diminution of boundary layer effects and thus reduced in-nozzle turbulence, and increased liquid jet velocity.